2020
DOI: 10.1088/2631-8695/abb4f3
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide—Polymethyl methacrylate coatings for Corrosion protection of aerospace aluminium alloy 7075—T651 surfaces

Abstract: We report a corrosion study on Al 7075—T651 surface. The purpose of the study is to use Graphene oxide—Polymethyl methacrylate (GO—PMMA) coating as corrosion resistant layer on Al 7075—T651, an alloy of aluminium mainly used in aerospace industries. The study is done with and without GO—PMMA coating on Al 7075—T651 respectively, by varying the exposure time of material (24, 48 and 72 h) with HCl in atmospheric condition. The formation of corrosion is resisted by the GO—PMMA coated samples. The effect is studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Graphene coatings protect substrates by blocking aggressive ions from contacting the surface with the aid of a physical barrier provided by graphene . This is due to the existence of the passivation layer and the dense filler–matrix interface, making the coating of PMMA with GO capable of preventing corrosion . Here, we discuss one of the promising previous studies of PMMA-GO for anticorrosive coating applications, as shown in Table .…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene coatings protect substrates by blocking aggressive ions from contacting the surface with the aid of a physical barrier provided by graphene . This is due to the existence of the passivation layer and the dense filler–matrix interface, making the coating of PMMA with GO capable of preventing corrosion . Here, we discuss one of the promising previous studies of PMMA-GO for anticorrosive coating applications, as shown in Table .…”
Section: Synthesis Methodsmentioning
confidence: 99%
“… 102 This is due to the existence of the passivation layer and the dense filler–matrix interface, making the coating of PMMA with GO capable of preventing corrosion. 103 Here, we discuss one of the promising previous studies of PMMA-GO for anticorrosive coating applications, as shown in Table 7 .…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…This effect is especially evident in aluminium alloys, and the coating by anticorrosion layers is therefore a pivotal subject of applied research. In this context, GO-based materials inserted in a polymeric matrix were demonstrated to improve the corrosion resistance of the applied layers ( Figure 4 ), likely due to the more compact coating-substrate interface [ 36 ].…”
Section: Emerging Applications and Open Challengesmentioning
confidence: 99%
“… Schematic representation of corrosion behaviour on Al samples; ( a ) corrosion behaviour on the uncoated sample, ( b ) corrosion behaviour on GO–PMMA coated sample (reproduced with permission from ref. [ 36 ]. Copyright© 2020 IOP).…”
Section: Figurementioning
confidence: 99%